Digital broadcasting : technology standards, and regulations - Bruin, Ronald; Smits, Jan. (New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing, 2015)
"Digital Broadcasting presents an introduction to how the classic notion of 'broadcasting' has evolved and is being reinterpreted in an age of digitization and convergence. The book argues that 'digital broadcasting' is not a contradiction in terms, but-on the contrary-both terms presuppose and need each other. Drawing upon an interdisciplinary and international field of research and theory, it looks at current developments in television and radio broadcasting on the level of regulation and policy, industries and economics, production and content, and audience and consumption practices"--
Include index
Includes bibliographical references (pages 129 -149) and index.
Keywords: Broadcasting -- History; Digital television; Digital audio broadcasting; Television broadcasting; Digital Radio broadcasting; Radio Broadcasting; LANGUAGE ARTS & DISCIPLINES / Journalism